New approaches in territorial development analysis - Torre, André (2020)
The relatively recent emergence of the term territorial development in the literature is largely related to the interest shown in recent years by researchers and policy makers for territorial questions. While research has long focused on regional dimensions and development processes at the national or regional level, a number of events have drawn attention to the issue of territories and highlighted all the interest to address the thorny but very popular problem of territorial development. Production and innovation are often at the forefront of this analysis, and it is less common to worry about governance issues. However, they occupy a decisive place, because the development processes involve participation or provoke opposition from the local populations. Indeed, the different actors of the territories must agree on the territorial projects and reach an agreement on the future developments of these spaces, as well as the major options for their future. The objective of this paper is to show the necessity to address the two drivers of territorial development, namely production and governance, and to analyze how they operate and their impact on the growth processes and the social and institutional changes that characterize them. We begin by presenting our definition of territorial development, before addressing successively its productive and governance dimensions, in order to chart the major paths of a renewed approach to the drivers of development and their main characteristics.